2007
DOI: 10.1161/strokeaha.107.483842
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 10 Different Magnetic Resonance Perfusion Imaging Processing Methods in Acute Ischemic Stroke

Abstract: Background and Purpose-Several methods are available to assess the magnetic resonance perfusion lesion in acute ischemic stroke. We tested 10 of these to compare perfusion lesion sizes and to assess the relation to clinical scores and final infarct extent. Methods-We recruited patients with acute ischemic stroke, performed diffusion-and perfusion-weighted imaging, and recorded stroke severity at baseline, final infarct size on T2-weighted imaging at Ն1 month, and Rankin Scale score at 3 months. We calculated 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
73
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(83 citation statements)
references
References 36 publications
7
73
0
3
Order By: Relevance
“…The type of deconvolution (Ostergaard et al, 1996;Wu et al, 2003) as well as the placement of the AIF (Ebinger et al, 2010a;Thijs et al, 2004) lack a standardized definition across the imaging facilities. The MRI studies (Kane et al, 2007a), comparative MR/PET studies Takasawa et al, 2008a;Zaro-Weber et al, 2010b) and Xenon computed tomography studies (Olivot et al, 2009b) showed that these different approaches to PW maps cause a high variability of flow values with a substantial influence on the resulting mismatch volumes. To attenuate this variability, calibration techniques for PW maps were used and could improve the reliability of perfusion measurement (Ostergaard et al, 1998;Takasawa et al, 2008a;ZaroWeber et al, 2010a).…”
Section: Imaging Of Hypoperfusionmentioning
confidence: 99%
See 1 more Smart Citation
“…The type of deconvolution (Ostergaard et al, 1996;Wu et al, 2003) as well as the placement of the AIF (Ebinger et al, 2010a;Thijs et al, 2004) lack a standardized definition across the imaging facilities. The MRI studies (Kane et al, 2007a), comparative MR/PET studies Takasawa et al, 2008a;Zaro-Weber et al, 2010b) and Xenon computed tomography studies (Olivot et al, 2009b) showed that these different approaches to PW maps cause a high variability of flow values with a substantial influence on the resulting mismatch volumes. To attenuate this variability, calibration techniques for PW maps were used and could improve the reliability of perfusion measurement (Ostergaard et al, 1998;Takasawa et al, 2008a;ZaroWeber et al, 2010a).…”
Section: Imaging Of Hypoperfusionmentioning
confidence: 99%
“…This heterogeneity includes the mismatch definition itself (Kane et al, 2007b), the choice of the PW map and the method of postprocessing (Kane et al, 2007a), the use of an automated processing software (Galinovic et al, 2011a), the delineation of core and hypoperfusion (Ay et al, 2008), and the predefined mismatch ratio (Kakuda et al, 2008). If the different definitions of mismatch would be applied to one patient sample, the variability in resulting mismatch volumes would clearly exceed 20% (Kane et al, 2007a)-more than the operationally defined minimum mismatch ratio required for therapeutic decisions (mismatch ratio 1.2) according to previous stroke studies (Albers et al, 2006;Davis et al, 2008).…”
Section: Mismatch: the Clinical Evidence Or 'Lost In Translation'?mentioning
confidence: 99%
“…Most studies used time-to-peak (TTP) or mean transit time maps for mismatch calculation because these parameters are robust and easy to obtain. [7][8][9][10][11][12][13] The MRI-based measurement of cerebral blood flow (CBF MRI ), although considered a close estimate of cerebral perfusion, 14 was applied in only few clinical studies. 13,[15][16][17][18][19][20][21] CBF MRI was mainly described with respect to infarct development on follow-up MRI that suffered from the uncertainty of perfusion changes between early MRI and follow-up imaging.…”
mentioning
confidence: 99%
“…The inaccuracy in defining the penumbra with the PWI/DWI mismatch is mainly related to the PWI, which uses variable parameters to estimate perfusion. As a consequence, the perfusion lesion size differs markedly depending on the parameters calculated [27] and is usually overestimated. Time-to-peak delays of 4 and 6 s reliably identify hypoperfused and exclude normoperfused tissue but overestimate the volume of critically perfused but salvageable tissue, i.e.…”
Section: Non-invasive Imaging Of the Penumbramentioning
confidence: 99%